2018
DOI: 10.1038/s41598-018-26017-z
|View full text |Cite
|
Sign up to set email alerts
|

Large positive linear magnetoresistance in the two-dimensional t 2g electron gas at the EuO/SrTiO3 interface

Abstract: The development of novel nano-oxide spintronic devices would benefit greatly from interfacing with emergent phenomena at oxide interfaces. In this paper, we integrate highly spin-split ferromagnetic semiconductor EuO onto perovskite SrTiO3 (001). A careful deposition of Eu metal by molecular beam epitaxy results in EuO growth via oxygen out-diffusion from SrTiO3. This in turn leaves behind a highly conductive interfacial layer through generation of oxygen vacancies. Below the Curie temperature of 70 K of EuO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 58 publications
(65 reference statements)
1
32
0
Order By: Relevance
“…Guo et al have also demonstrated growth of EuO on Si, in which a STO buffer was used to mediate epitaxy . Interestingly, the STO buffer layer also served as a source of oxygen during growth of the EuO film …”
Section: Materials and Functional Propertiesmentioning
confidence: 99%
“…Guo et al have also demonstrated growth of EuO on Si, in which a STO buffer was used to mediate epitaxy . Interestingly, the STO buffer layer also served as a source of oxygen during growth of the EuO film …”
Section: Materials and Functional Propertiesmentioning
confidence: 99%
“…Furthermore, we can see an increase in MR with decreasing temperatures. At 10 K, the MR is about 40.5% at a high field of 10 T. More interestingly, the MR has a linear relation with the applied magnetic field at 10 K, while it has a roughly quadratic relation at T ≥ 20 K. We ascribe the origin of the positive linear MR to a Zeeman split of the electronic structure induced by magnetic ordering of oxygen vacancies, which is similar with the EuO/SrTiO 3 interface . The quadratic dependence of MR can be attributed to the ordinary Lorentz contribution which can increase the defect scattering from the enhanced transit path of electrons .…”
mentioning
confidence: 66%
“…The first‐suggested electronic reconstruction model, based on the charge mismatch (polar catastrophe) between the constituent cations, indicated that the 2DEG is localized at the topmost part of the STO substrate . There were several reports, however, that the nonpolar capping layer, such as amorphous LAO, yittria‐stabilized ZrO 2 , CaHfO 3 , amorphous Al 2 O 3 ( a ‐AO), and even ultrathin metal films, could feasibly produce the 2DEG on the similar STO substrate. These heterostructures are free from the charge mismatch effect, and as such, the electron accumulation at the interface cannot be induced by the suggested polar catastrophe effect.…”
Section: Summary Of the Fitting Results Obtained From Arxps The Calcmentioning
confidence: 99%
“…ultrathin metal films, [13,14] could feasibly produce the 2DEG on the similar STO substrate. These heterostructures are free from the charge mismatch effect, and as such, the electron accumulation at the interface cannot be induced by the suggested polar catastrophe effect.…”
mentioning
confidence: 99%